2019
DOI: 10.1108/ijppm-10-2018-0376
|View full text |Cite
|
Sign up to set email alerts
|

Modeling teachers’ quality of work life: a partial least square approach

Abstract: Purpose The purpose of this paper is to examine the factors affecting quality of work life (QWL) of teachers working in Higher Education Institutions. Design/methodology/approach A cross-sectional study was conducted by sampling 347 teaching faculty members through questionnaires. Findings Fair communication plays the strongest role and social networks have the weakest role in shaping the QWL in higher educational institutions (HEIs) of Pakistan. The relationship of social networks and QWL negates the Hofs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 67 publications
(83 reference statements)
1
6
0
Order By: Relevance
“…First, the results confirm that hotels' organizational justice has a significant influence on the quality of operational employees' work life in Bangladeshi hotels. This result is in line with the results of prior research that exhibited the positive association between firms' organizational justice and employees' worklife quality (Gillet et al, 2013;Malik et al, 2019;Rai, 2015). These studies demonstrated how an organization's justice practices promote employees' peaceful lives at work.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…First, the results confirm that hotels' organizational justice has a significant influence on the quality of operational employees' work life in Bangladeshi hotels. This result is in line with the results of prior research that exhibited the positive association between firms' organizational justice and employees' worklife quality (Gillet et al, 2013;Malik et al, 2019;Rai, 2015). These studies demonstrated how an organization's justice practices promote employees' peaceful lives at work.…”
Section: Discussionsupporting
confidence: 90%
“…They concentrate on both individuals and organizations as a whole (Rai, 2015). The fair practices of resource allocation and compensation, and justice in organizational procedures and policies result in employee well-being, job satisfaction, and enhanced QWL (Brunault et al, 2014;Gillet et al, 2013;Malik et al, 2019;Moghimi et al, 2013;Rai, 2015). Furthermore, the availability of fair treatment in the organization fosters employee-organizational trust and limits the adoption of work-deviant behaviors (Malik et al, 2019;Rai, 2015;Sahoo & Sahoo, 2019).…”
Section: Organizational Justice and Quality Of Work Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports showed that the quality of working life is influenced by spiritual intelligence mediated by psychological capital (Singla et al, 2021). Another example given in a study involving 345 Pakistani teachers reported that communication is an influential factor in the quality of work life (Malik et al, 2019). Similarly, it is the individual factors that affect the quality of work life of teachers when considering motivation, adaptation, communication, and experience, among others (Ghashghaeizadeh, 2020).…”
Section: Factors Affecting the Quality Of Life At Workmentioning
confidence: 99%
“…The benefits of QoWL are closely linked to both employees and employers, who are involved in learning more and more about the factors that positively or negatively influence the working life of workers [32][33][34][35]. At the same time, all employees are sensitive to the changes and improvements the entity can promote in the work environment [36].…”
Section: Introductionmentioning
confidence: 99%